Incidence of postoperative atrial fibrillation in patients undergoing on-pump and off-pump coronary artery bypass grafting - Bohatch Júnior,Milton Sérgio (2015)
AbstractObjective:To determine the incidence of postoperative atrial fibrillation in patients undergoing on-pump and off-pump coronary artery bypass grafting.Methods:A retrospective study with analysis of 230 medical records between January 2011 and October 2013 was conducted.Results:Fifty-six (24.3%) out of the 230 patients were female. The average age of patients undergoing on-pump coronary artery bypass grafting was 59.91±8.62 years old, and off-pump was 57.16±9.01 years old (P=0.0213). The average EuroSCORE for the on-pump group was 3.37%±3.08% and for the off-pump group was 3.13%±3% (P=0.5468). Eighteen (13.43%) patients who underwent off-pump coronary artery bypass grafting developed postoperative atrial fibrillation, whereas for the onpump group, 19 (19.79%) developed this arrhythmia, with no significant difference between the groups (P=0.1955).Conclusion:Off-pump coronary artery bypass grafting did not reduce the incidence of atrial fibrillation in the postoperative period. Important predictors of risk for the development of this arrhythmia were identified as: patients older than 70 years old and presence of atrial fibrillation in perioperative period in both groups, and non-use of beta-blockers drugs postoperatively in the on-pump group.